Design and fabricate motorized mini cultivator - Ahmad Fuad, Muhammad Yusof (2025)
This study aims to design a mini cultivator to help farmers clean up or recreate a ditch or trench in between paddy fields. The problem faced by using an excavator is money and rain, as well as unclear vision and the weight of the machines. The scope of the study is to design the mechanical part for the mini cultivator, analyse the maximum force and weight that can be accommodated, and fabricate the mini cultivator using steel, bearings, and lawn mower engine. The significance of the project is to help farmers become more efficient and faster during the gap between replanting and harvesting.